Chromatin accessibility in canine stromal cells and its implications for canine somatic cell reprogramming. (16th November 2020) - Questa, Maria; Moshref, Maryam; Jimenez, Robert J.; Lopez-Cervantes, Veronica; Crawford, Charles K.; Settles, Matthew L.; Ross, Pablo J.; Kol, Amir
Abstract: Naturally occurring disease in pet dogs is an untapped and unique resource for stem cell-based regenerative medicine translational research, given the many similarities and complexity such disease shares with their human counterparts. Canine-specific regulators of somatic cell reprogramming and pluripotency maintenance are poorly understood. While retroviral delivery of the four Yamanaka factors successfully reprogrammed canine embryonic fibroblasts, adult stromal cells remained resistant to reprogramming in spite of effective viral transduction and transgene expression. We hypothesized that adult stromal cells fail to reprogram due to an epigenetic barrier. Here, we performed assay for transposase-accessible chromatin using sequencing (ATAC-seq) on canine stromal and pluripotent stem cells, analyzing 51 samples in total, and establishing the global landscape of chromatin accessibility before and after reprogramming to induced pluripotent stem cells (iPSC). We also studied adult stromal cells that do not yield iPSC colonies to identify potential reprogramming barriers. ATAC-seq analysis identified distinct cell type clustering patterns and chromatin remodeling during embryonic fibroblast reprogramming. Compared with embryonic fibroblasts, adult stromal cells had a chromatin accessibility landscape that reflects phenotypic differentiation and somatic cell-fate stability. We ultimately identified 76 candidate genes and several transcription factor binding motifs that may be impeding somatic cell reprogramming to iPSC, and could be targeted for inhibition or activation, in order to improve the process in canines. These results provide a vast resource for better understanding of pluripotency regulators in dogs and provide an unbiased rationale for novel canine-specific reprogramming approaches. Abstract : Canine embryonic fibroblasts are successfully reprogrammed, but adult stromal cells remain resistant, likely due to epigenetic barriers. We performed assay for transposase-accessible chromatin using sequencing on canine stromal cells and pluripotent stem cells, and identified distinct chromatin remodeling patterns. We identify candidate genes and transcription factor binding motifs that may be impeding adult cell reprogramming, and could be targeted to improve protocols in canines.